A Conceptual Metaphor Study of The Song of Annabelle Dinda’s "The Hand" - Agnes Dhea Oktavia Sinaga; T. Thyrhaya Zein; Sarah Anastasia; Sari Gracya Laura Sianturi; Tria Amelia Surbakti; Isnaila Ramadhani (IKRA-ITH ABDIMAS, 2026)
Song lyrics represent a rich site for the study of conceptual metaphor, as they condense complex emotional and social experiences into figurative language that reflects broader cultural values. Despite growing scholarly interest in metaphor within popular music, studiesexamining how gender inequality is constructed through metaphorical language in contemporary songwriting remain limited, particularly in relation to works by emerging artists. This study aims to identify, classify, and interpret the conceptual metaphors present in "TheHand" by Annabelle Dinda, with particular attention to how these metaphors construct and reinforce representations of gender inequality in artistic expression. A qualitative approach was employed, using document analysis as the primary method of data collection andfollowing Creswell's framework for qualitative data analysis. The metaphorical expressions identified in the lyrics were analyzed using Conceptual Metaphor Theory, with each expression examined through the mapping between its source and target domains andorganized according to three major metaphor types, namely structural, ontological, and orientational metaphors. The analysis identified eleven metaphorical expressions across the lyrics, with structural metaphors appearing most frequently, followed by ontologicaland orientational metaphors. The findings reveal that these mappings work collectively to expose the gendered double standard in how male and female voices are culturally positioned, evaluated, and constrained within the creative domain. These results suggest thatsong lyrics function not merely as aesthetic objects but as discursive sites in which ideological constructions of gender inequality are both reproduced and critically questioned.Keywords: conceptual metaphor, gender inequality, song lyrics